Status Hara Nitrogen, Fosfor, dan Kalium pada Lahan Sawah di Desa Savana Jaya Kecamatan Waeapo Kabupaten Buru - Wamnebo, Siti I R; Kaya, Elizabeth; Siregar, Adelina (Universitas Pattimura, 2023)
is research aims to study nutrients status of N, P, and K in Savana Jaya Village, District of Waeapo, Buru Regency. This research was descriptive and using survey method in the field. Soil samples were composited taken from 5 subsites with 25 m distance from sampling center point. Respondents were selected by using a purposive sampling method, and production data was collected by interviewing farmers. The results showed that the total N status in the Savana Jaya village was low (0,10-0,12%) to very low (0,09%), total P status was moderate (23-38 mg/100 g) to very high (68 mg/100 g), and total K status was low (10-13 mg/100 g) to moderate (30 mg/100 g). The proposed balanced-fertilizer management to support rice fields in the study area is site-specific nutrient management (PHSP) using NPK compound fertilizers combined with urea, Ponsta and Pelangi fertilizers based on nutrients and soil fertility status in the study area, including adding lime to increase soil pH, adding petrorganic organic matter to increase soil C-Organic and soil CEC.